Roads to remission: evolving treatment concepts in type 2 inflammatory diseases - Marek Lommatzsch; Katharina Blumchen; Lisa A. Beck; Jean Bousquet; Guy G. Brusselle; Wytske J. Fokkens; Eckard Hamelmann; Susanne Lau; Hagen Ott; Oliver Pfaar; Hugh A. Sampson; Josef S. Smolen; et al. (EClinicalMedicine)
Summary: Non-communicable diseases (NCDs) characterised by type 2 inflammation, including asthma, allergic rhinitis, chronic rhinosinusitis with nasal polyps, atopic dermatitis, food allergies and eosinophilic esophagitis, are increasing in prevalence worldwide. Currently, there is a major paradigm shift in the management of these diseases, towards the concept of disease modification and the treatment goal remission, regardless of severity and age. Remission as a treatment goal in chronic inflammatory NCDs was first introduced in rheumatoid arthritis, and then adopted in other non-type 2 inflammatory diseases. Among diseases with type 2 Inflammation, this concept is novel and currently most advanced in asthma. This new paradigm has been developed based on a better understanding of the pathophysiology of type 2 inflammation and the advent of highly effective drugs selectively interfering with type 2 pathways. Here, we review the evolution of the new remission concepts in type 2 inflammatory diseases and discuss associated challenges and future research needs. Funding: None.